Ethical reflexivity in qualitative research: the use of cinematographic movies as an instrument for continuous training - Doris Gomes; Juliara Bellina Hoffmann; Mirelle Finkler
ABSTRACT Objectives: to analyze ethically, aesthetically and politically the cine-debate of the movie "Human", reflecting on training of researchers in qualitative research. Methods: the debate about moral questions as the essence of humanity was based on Narrative Bioethics; the comprehensive, relational and reflective character of qualitative methods; and the ethical and social sense of qualitative researches. Results: the narratives of the experiences of morality, loaded with facts and valuations, highlighting the importance of reflexivity in all phases of the qualitative research process, from thinking about themes and research questions to fieldwork, from data analysis to the production of reports, fostering the researcher's responsibility both in the intervention for understanding and narrating the world, and in its possible transformation. Final Considerations: cinematographic art becomes an instrument of reflexivity capable of affecting and mobilizing students, in a fusion of horizons of understanding of different universes that dialogue.